Evaluation of Influenza Vaccine Effectiveness from 2021 to 2024: A Guangdong-Based Test-Negative Case–Control Study - Liyan Zhu; Ying Han; Jiahai Lu; Jianhao Tan; Conghui Liao; Cheng Guo; Qing He; Yajie Qiu; Huahua Lu; Yue Zhou; Jianrui Wei; Dandan Hu (Vaccines)
Background: The influenza virus’s high mutation rate requires the annual reformulation and administration of the vaccine. Therefore, its vaccine effectiveness (VE) must be evaluated annually. Aim: Estimate the effectiveness of the influenza vaccine and analyze the impact of age, seasonal variations, and the vaccination to sample collection interval on VE. Methods: The study used a test-negative case–control (TNCC) design to collect data from patients under 18 years of age who presented with acute respiratory infection (ARI) symptoms and underwent influenza virus testing at a national children’s regional medical center in Guangdong Province between October 2021 and January 2024, spanning three influenza seasons. VE was estimated using unconditional logistic regression. Results: A total of 27,670 patient data entries were analyzed. The VE against all influenza viruses across the three seasons was 37% (95% CI: 31–43), with the lowest VE of 24% (95% CI: 8–37) observed in the 2021–2022 season. In children aged 0.5 to <3 years, the VE was 32% (95% CI: 19–43). The effectiveness for samples collected at intervals of 0.5–2 months, 3–6 months, and over 6 months after vaccination was 39% (95% CI: 32–46), 30% (95% CI: 19–40), and 28% (95% CI: 5–46). Conclusions: Across three influenza seasons, at least one-third of vaccinated individuals were protected from influenza in outpatient settings. Given that children are at high risk, improving vaccination management is recommended, and parents should be encouraged to vaccinate their children before each influenza season.